An investigation of drug-induced mental disorders in the children and adolescents population utilizing the FDA adverse event reporting system - Linlin Tang; Qian Li; Xue Zhao; Liangxia Ding; Hui Li; Chuanhua Ding; Lijuan Teng (Scientific Reports)
Abstract Drug-induced mental disorders in children and adolescents are a significant concern, and the relationship between medications and severe mental disorders is not well understood. Utilizing the U.S. Food and Drug Administration’s Adverse Event Reporting System (FAERS), a comprehensive real-world investigation of drug-induced psychiatric disorders in children and adolescents is conducted. We reviewed all adverse event (AE) reports related to mental disorders in children and adolescents in the FAERS database from 2004 to 2024. After data cleansing and standardization, we quantified the statistical association between drugs and mental disorders using the Reporting Odds Ratio (ROR) method. A total of 29,622 AE reports related to drug-induced mental disorders in children and adolescents were identified in the FAERS database, uncovering 252 drugs with positive signals for mental disorders. These medications are primarily used to treat conditions such as Attention Deficit Hyperactivity Disorder (ADHD), psychiatric disorders, acne, asthma, allergic diseases, narcolepsy, contraception, and constipation. Our analysis revealed potential associations between various drugs and mental disorders, with isotretinoin, montelukast, risperidone, methylphenidate, atomoxetine and antidepressants showing higher ROR values, indicating a possible risk of mental disorders. Additionally, we found that some drugs did not explicitly list the risk of mental disorders in their instructions for use.